Penguatan Manajemen UMKM di Bali: Studi Kasus di Putra Susila Krupuk Kulit Ikan Tuna - Titisari, Kartika Hendra; Wijayanti, Anita; Damayanti, Ratna; Hadi, Pramono; Kristianto, Joko; Astuti, Partini Dwi; Darmadi, Ni Made (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
Implementation of community service in national collaboration, collaboration between Batik Islamic University, Surakarta and Warmadewa University, Denpasar, Bali. It was carried out on February 6 2024, at Putra Susila UMKM which produces tuna skin crackers with an address in Denpasar, Bali. The method of community service is carried out using a mentoring method carried out jointly between the Batik Islamic University Surakarta team and Warmadewa University Denpasar. Meanwhile, supporting factors include: related to production, storage of raw materials, layout of cooking areas, packing and sales. The analysis used is triangulation of primary data, theory and expert opinion. From the results of community service, a conclusion can be drawn that assistance still needs to be provided regarding raw materials which are still fluctuating, sometimes abundant, sometimes empty, so raw material storage technology is needed. Layout techniques and production space are good, neat and separate from the household. Packing has several inputs, namely that it is not big enough. Marketing is still around Denpasar with pre-order patterns and product displays and participating in exhibitions.